Permissibility of Death Penalty as a Hermeneutic Dilemma - Kosche, Michał (Verbum Vitae, 2020)
The notion of moral fairness of application of capital punishment is stretched between two poles of opposite interpretative meanings. On the one hand, there is an imperative related to maintaining the social order and good that justifies in some specific cases killing an individual for the good of the community; on the other hand, there is the message of the Gospel about holiness of each human life. In this regard, at the attempt to investigate the fairness of death penalty, a certain hermeneutic tension related to the overlapping of rights and obligations both with regard to the criminal and society that needs to be protected against him or her. The starting point of this article is an outlook on death penalty with due regard of a ‘hermeneutic charge’ contained both in the duty to protect common good and each individual’s life. Next, the ‘genuine paradox’ was analysed that emerges in a situation where the right to live and the right to protect overlap. All the considerations are concluded with a question whether the recent abolitionist interpretation of the Catechism of the Catholic Church should be classified as the continuity hermeneutic or rather the discontinuity hermeneutic.